Multinational Andean Project (MAP): Geological co-operation across borders - Getsinger, Jennifer; Hickson, Catherine (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2000)
Summary One of the world's largest and most spectacular continental areas of rhyolitic-andesitic volcanic rocks, the Neogene-Quaternary central Andes volcanic complex, occurs in the high Andes mountains of South America. More than1000 eruptive centres, many hostingsignificant mines and occurrences ofepithermal precious metals, as well as other metals and industrial minerals, underlie the Andean border regions of Argentina, Bolivia, Chile, and Peru. Many mining companies are actively exploring the area, including a large number of Canadian-based companies. The Multinational Andean Project (MAP), funded by the Canadian International Development Agency and the national governments of Argentina, Bolivia, Chile, and Peru and facilitated by the Geological Survey of Canada, is an important international initiative for Canada in terms of scientific exchange and fostering enhanced relationships between Canadian and South American national geoscience agencies and mineral exploration companies. Now inthe final year of the five year project, MAPwill have a long lasting scientific legacy in the form of geological and metallogenic maps consistent across international boundaries, a multicountry analytical geochemical data base, penologicalreference materials for Andean volcanicrocks, extensive geophysical survey information, and scientific publications.The high level of co-operation established among the participating countries provides an excellent model for future international projects.